Modeling and Simulation in Industrial Engineering (Management and Industrial Engineering,, 2018)
This book describes the latest research developments in modeling and simulation in industrial engineering. Topics such as decision and performance analysis and industrial control systems are described. Case studies in industry and services as well as engineering economy and cost estimation are also covered.